2012
DOI: 10.1038/emboj.2012.315
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric activation of exopolysaccharide synthesis through cyclic di-GMP-stimulated protein–protein interaction

Abstract: In many bacterial pathogens, the second messenger c-di-GMP stimulates the production of an exopolysaccharide (EPS) matrix to shield bacteria from assaults of the immune system. How c-di-GMP induces EPS biogenesis is largely unknown. Here, we show that c-di-GMP allosterically activates the synthesis of poly-b-1,6-N-acetylglucosamine (poly-GlcNAc), a major extracellular matrix component of Escherichia coli biofilms. C-di-GMP binds directly to both PgaC and PgaD, the two inner membrane components of the poly-GlcN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
154
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(158 citation statements)
references
References 80 publications
4
154
0
Order By: Relevance
“…Recent studies also have demonstrated homo-and heteromeric complexes between cell wall-synthesizing enzymes, i.e. chitin, cellulose, and poly-␤-1,6-N-acetylglucosamine synthases (29,31,32). These enzymes resemble HASs in that they are also thought to form a pore in plasma membrane for extrusion of the growing polysaccharide chain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies also have demonstrated homo-and heteromeric complexes between cell wall-synthesizing enzymes, i.e. chitin, cellulose, and poly-␤-1,6-N-acetylglucosamine synthases (29,31,32). These enzymes resemble HASs in that they are also thought to form a pore in plasma membrane for extrusion of the growing polysaccharide chain.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the extrusion pore of the poly-␤-1,6-N-acetylglucosamine synthesis machinery of Yersinia pestis (28) and Escherichia coli (29) is suggested to require the formation of a heterodimer with altogether 6 transmembrane domains. On the other hand, channels such as lactose permease contain 12 transmembrane ␣-helices (30), whereas the two protein subunits of bacterial cellulose synthase contain altogether 9 transmembrane domains and couple polymerization with membrane penetration (31).…”
mentioning
confidence: 99%
“…This constitutes a plausible system for transcriptional control, thus it appears that PGA is subject to both transcriptional control and post-translational control. In E. coli, c-di-GMP functions primarily as an allosteric activator that binds directly to PgaC and PgaD to increase glycosyltransferase activity (Steiner et al, 2013). The presence of a homologous two-component system (PA4032 and PA4036) in P. aeruginosa, which lacks the pgaABCD genes, suggests that the PFLU0005-PFLU0007 system might not exclusively regulate PGA expression or that its regulatory role is indirect.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, PgaD, a small membrane protein with two predicted transmembrane helices, assists the glycosyltransferase in polymerizing PNAG and is involved in the regulation of PNAG synthesis. The two inner membrane proteins PgaC and PgaD form a complex that functions as a novel type of c-di-GMP receptor wherein ligand binding to the two proteins stabilizes their interaction and allosterically activates PNAG synthesis (25). The expression of the E. coli pgaABCD operon is tightly regulated.…”
mentioning
confidence: 99%